Todos tus muertos - Moreno, Carlos; Torres, Alonso; Rodríguez, Álvaro (Actor); Herrera, Jorge, 1948-; Márquez, Martha, 1975-; Vasten, Harold de; Castillo, John Alex, 1977-; Zúñiga, Jorge E.; Gallego, Santiago; Jiménez, Diego; Porras, Andrés (64-a Films, 2011)
In this eerie and fantastically shot tragicomic satire, an ordinary farmer's morning routine is interrupted when he makes a grim discovery in the middle of his cornfield--a huge pile of dead bodies. Aghast, he reports the mysterious massacre on what happens to be Election Day. When the small-town mayor and police lieutenant take notice, fearful of unleashing a public scandal, they stall and intimidate the farmer and his family. Meanwhile, the sun beats down, and the eerie corpses remain, refusing to be ignored. --